Effect of laparoscopic sleeve gastrectomy on vitamin D, parathormone hormone, and serum calcium levels - Reda Fawzy Ali; Khalid Ahmed Ismail; Taha Ahmed Ismail; Ahmed Lamey Ahmed Saleh; Ahmed Mahmoud Aouf; Mohamed Ahmed Tolba ElKhopy (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the effect of laparoscopic sleeve gastrectomy on vitamin D status, parathyroid hormone, serum calcium and the effectiveness of vitamin D supplementation. Method: The prospective study was conducted at the General Surgery Department of Kafrelsheikh University Hospital, Egypt, in November 2019, and comprised morbidly obese patients of either gender who were managed with laparoscopic sleeve gastrectomy. Serum levels of vitamin D, calcium and parathyroid hormone were assessed at baseline and at 6 and 12 months after the surgery. All subjects were given 400 IU/day of vitamin D. If the level of vitamin D was <30ng/ml, further doses of calcifediol 200,000 IU were added every two weeks. Data was analysed using SPSS 22. Results: Of the 40 patients, 28(70%) were females and 12(30%) were males. The overall mean age was 33.9±10.8, mean weight was 136±18.29kg and mean body mass index was 50±4.9kg/m2. The mean operative time was 64.5±13.6 minutes, and the mean hospital stay was 1.8±1.1 days. There was significant reduction in body mass index values after the surgery (p<0.05). Vitamin D level was 19.2±3.2 ng/ml at baseline, which rose to 21.4±2.7 ng/ml at 6 months and 26.6±2.8 ng/ml at 12 months post-surgery (p<0.05). Preoperative parathyroid hormone level was 58.3±7.8 pg/ml , which went down to 48.6±7.4 pg/ml at 6 months, and 41.3±6.5 pg/ml at 12 months postoperatively (p<0.05). The mean serum calcium level at baseline was 9±0.4mg/dL, which rose to 9.2 ±0.3mg/dL and 9.5±0.4 mg/dL at 6 and 12 months post-surgery (p<0.05). Conclusion: Low vitamin D complications could be decreased postoperatively by administering vitamin D as a routine treatment. Postoperative monitoring of vitamin D, parathyroid hormone and serum calcium levels is essential. Keywords: Obesity, Morbid, Parathyroid hormone, Gastrectomy, Laparoscopy, Bariatrics. Registration: RCT registered at: clinicaltrials.gov (NCT05430932)